Employee Performance Improvement through Employee Empowerment and Employee Organization Learning in Semarang Tengah District, Semarang City - Prasetyo, Prasetyo; Suparmi, Suparmi (Untag Business and Accounting Review, 2022)
Optimal public service activities that will be carried out by local government organizations such as sub-districts require qualified state civil servants. This study aims to analyze the effect of employee empowerment and organizational learning on employee performance. The population of this research is employees in Central Semarang District as many as 158 people, the number of samples is 123 people who are selected by using proportional random sampling. The analysis technique used is multiple linear regression with SPSS Version 22. The results show that employee empowerment and organizational learning have a significant effect on employee performance.